Onoceranoid Triterpene from Langsep Leaf (Lansium domesticum Corr.) and Its Insecticide Activity to Spodoptera littura Larvae - Winata, I Nyoman Adi; Sjaifullah, Achmad; Cahyani, Dita J.; Ayu, Woro D. (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2017)
Onoceranoide type of triterpene was isolated from leaf of langsep (Lansium domesticum Corr.) Isolation is conducted by vacuum and flash column chromatography technics with Silika Gel 60 F, Silika Gel 60 (70-230 mesh), and Sephadex LH-20 powder as stationery phase and mixture of dichloromethane, methanol, ethyl acetate as mobile phase. The structure was identified by Infrared and NMR spectroscopy. It has moderate insecticidal activity to Spodoptera littura larvae with LC50 13,6 ppm.